Prescribing Drugs not in Accordance with the Official Instructions for Medical Use (Off-label), Clinical Guidelines, Standards of Medical Care and Legal Regulation in the Russian Federation. Part 2 - A. R. Navasardyan; S. Yu. Martsevich; P. G. Gabay (Столичная издательская компания, 2021)
Prescribing drugs not in accordance with the official instructions for medical use (off-label) has medical and legal aspects. From a medical point of view, such an appointment can be dictated by clinical urgency, when there is no alternative therapy, and on the other hand, doctors often prescribe off-label drugs unknowingly, and also when there is another drug with registered indications. The article analyzes the regulations governing such appointments. The article describes possible inconsistencies between clinical guidelines and standards of medical care in this matter, the role of the medical commission, the impact on the quality and safety of medical care, as well as the types of legal liability of a medical worker that may arise when a drug is prescribed not according to instructions.